2019
DOI: 10.1177/0194599819852328
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Bleeding Associated with Ibuprofen Use after Tonsillectomy: A Meta‐analysis

Abstract: Objective To better quantify the risk of ibuprofen-associated posttonsillectomy hemorrhage (PTH). Data Sources PUBMED/MEDLINE, Web of Science, and Cochrane Clinical Trials Database. Review Method Literature searches were performed for English-language publications containing the terms tonsillectomy, ibuprofen, and tonsillectomy from database inception to May 2017. Human clinical trials, prospective cohort studies, and retrospective cohort studies related to tonsillectomy, ibuprofen use, and posttonsillectomy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 31 publications
3
39
0
Order By: Relevance
“…According to Stokes et al, none of the previous literature on Ibuprofen use post-tonsillectomy contained measures that proved that the patients were given the prescribed medications. 13 Finally, our study could have been improved by collecting data over the course of more than 18 months to ensure that the results of our novel treatment plan did not regress to the previous mean, and that improvements were sustained over many years and many different surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Stokes et al, none of the previous literature on Ibuprofen use post-tonsillectomy contained measures that proved that the patients were given the prescribed medications. 13 Finally, our study could have been improved by collecting data over the course of more than 18 months to ensure that the results of our novel treatment plan did not regress to the previous mean, and that improvements were sustained over many years and many different surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…2 A meta-analysis was carried out in 2019 which suggested a slightly elevated incidence of bleeding when Ibuprofen was used for post-tonsillectomy analgesia and suggested a multi-institutional RCT is needed to determine if Ibuprofen actually increases the risk of PTH. 13 Because of the importance of this concern, a Quality Improvement study with regard to Acetaminophen and Ibuprofen dosing was carried out in our practice in order to see if we could rapidly improve patient outcomes for those undergoing tonsillectomy. We hypothesized that reducing the total doses of Ibuprofen would improve PTH rate.…”
Section: Introductionmentioning
confidence: 99%
“…20 Other analyses that had a higher risk of bias because of observational study design identified a small but statistically significant increase in bleeding (OR, 1.38; CI, 1.11-1.72). 21 More recently, Diercks et al 22 completed a multicenter randomized controlled trial of 741 children undergoing tonsillectomy and/or adenotonsillectomy that randomized children to either ibuprofen 10 mg/kg or acetaminophen 15 mg/kg, with a primary outcome of rate of post-tonsillectomy bleeding requiring a return to the operating room. The authors found a rate of postoperative bleeding requiring a return to the operating room of 1.2% in the acetaminophen group and 2.9% in the ibuprofen group ( P = 0.12), but all patients in the study took ibuprofen every 6 hours for 9 days, which is far in excess of what is commonly used in practice.…”
Section: Discussionmentioning
confidence: 99%
“…22 Another meta-analysis found increased bleeding with ibuprofen but required a sample size of 319,305 patients to reach significance. 21…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our current study, the authors were able to detect a statistically significant increase in PTH, with a similar OR of 1.38. 24…”
Section: Discussionmentioning
confidence: 99%